A Boron Doped Diamond Electrode Modified with Nano‐carbon Black for the Sensitive Electrochemical Determination of Chlorogenic Acid. Issue 12 (7th August 2019) - Teker, Tugçe; Hasan, Ali Mahmood Hasan; Aslanoglu, Mehmet
Abstract: An electrochemical method was developed for the sensitive determination of chlorogenic acid using a boron doped diamond electrode (BDDE) modified with nano‐carbon black (nano‐CB). The active surface areas were found to be 0.059 and 0.146 cm 2 for the unmodified BDDE, and nano‐CB/BDDE, respectively. Compared with a BDDE, the nano‐CB/BDDE exhibited a well‐defined redox couple for chlorogenic acid. In addition, the plot of the peak current response changing from a square root to a linear dependence on scan rate is attributed to the transition from planar diffusion to surface behaviour. The anodic and cathodic peak separations (ΔEp ) were 97 mV and 14 mV at BDDE and nano‐CB/BDDE, respectively. The decrease in ΔEp at the proposed electrode indicated that the process of chlorogenic acid was greatly accelerated. Square wave voltammetry (SWV) exhibited a dynamic range in which the current versus the concentration of chlorogenic acid were linear from 2.0×10 −8 to 2.0×10 −6  M with a LOD of 4.1×10 −9  M (based on 3Sb /m). The nano‐CB modified BDDE provided improved electrochemical behavior, high electrocatalytic activity, high sensitivity and good reproducibility. Abstract :